2020
DOI: 10.1038/s41598-020-68861-y
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results in the analysis of the immune response after aneurysmal subarachnoid hemorrhage

Abstract: Cerebral vasospasm (VSP) is a common phenomenon after aneurysmal subarachnoid hemorrhage (aSAH) and contributes to neurocognitive decline. The natural history of the pro-inflammatory immune response after aSAH has not been prospectively studied in human cerebrospinal fluid (CSF). In this pilot study, we aimed to identify specific immune mediators of VSP after aSAH. Peripheral blood (PB) and CSF samples from patients with aSAH were prospectively collected at different time-points after hemorrhage: days 0–1 (acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…Given that complications like DCI and DCI-related infarctions, which have been proposed to be the result of microvascular dysfunction in the brain, are typically restricted to the first two or at most 3 weeks after the ictus as well, these findings support the assumption that retinal vessels could serve as a surrogate marker for changes in cerebral small vessels after aSAH. The observed time-course also matches the pathophysiological cascades traditionally thought to be responsible for vascular dysfunction after aSAH, namely hemolysis of subarachnoid blood and intrathecal immune activation during the early phase, secondary immune infiltration and formation of various vasoactive hemoglobin metabolites during the critical phase and their gradual clearance during the late phase ( 42 44 ). Further support for the idea comes from recent discovery of cerebral and retinal glymphatic systems ( 22 ), which could provide a perivascular pathway through which vasoactive agents formed during the critical phase reach the retinal microvasculature.…”
Section: Discussionsupporting
confidence: 75%
“…Given that complications like DCI and DCI-related infarctions, which have been proposed to be the result of microvascular dysfunction in the brain, are typically restricted to the first two or at most 3 weeks after the ictus as well, these findings support the assumption that retinal vessels could serve as a surrogate marker for changes in cerebral small vessels after aSAH. The observed time-course also matches the pathophysiological cascades traditionally thought to be responsible for vascular dysfunction after aSAH, namely hemolysis of subarachnoid blood and intrathecal immune activation during the early phase, secondary immune infiltration and formation of various vasoactive hemoglobin metabolites during the critical phase and their gradual clearance during the late phase ( 42 44 ). Further support for the idea comes from recent discovery of cerebral and retinal glymphatic systems ( 22 ), which could provide a perivascular pathway through which vasoactive agents formed during the critical phase reach the retinal microvasculature.…”
Section: Discussionsupporting
confidence: 75%
“…The potent homeostatic function of Tregs in the peripheral immune system involves the inhibition of early immune overactivation that may result in an exhausted immune phenotype ( 62 ). In contrast, Th17 cells promote the inflammatory response ( 63 ) and are an important source of pro-inflammatory cytokines to aggravate brain injury ( 64 ).…”
Section: Pathophysiological Mechanismmentioning
confidence: 99%
“…In the delayed phase (10 days after SAH), M1 microglia are converted to M2 phenotype characterized by scavenging debris, expression of anti-inflammatory molecules, and promoting angiogenesis. Despite the finding that BBB is altered after SAH, the majority of Iba1-positive cells 5 days following SAH are Ccr2 − /Cx3cr1 + cells, suggesting that resident microglia rather than peripheral immune cells are the cellular mediators of inflammation in the CNS after SAH [ 312 , 355 , 356 ]. Similar results were published by Xu et al, who found that CCR2 macrophages do not enter until at least 48 h following induction of SAH [ 357 ].…”
Section: Reaction To Sah Of Neurovascular Unit Cellsmentioning
confidence: 99%